Los “daños punitivos” y su incorporación al derecho peruano: reflexión acerca de su utilidad en procesos por daños masivos - Alcántara Francia, Olga Alejandra (2021)
Objective: This article raises a reflection on the incorporation of the Anglo-Saxon figure of “punitive damages into the Peruvian consumer law “ in order to eliminate cases in which the behavior of the offender expressed in indifference, disinterest, etc., towards the victim is not punished and may even constitute a profitable activity. Methodology: Hermeneutic-synthetic methodology for the characterization of the cases of private punishment, administrative sanctions and mandates. Application of the compared method in the evaluation of its implementation in the jurisdiction and/or in sanctioning administrative headquarters. Results: Its adoption, through consumer arbitration for the cases of protection of interests and in judicial proceedings for the protection of diffuse interests, can generate positive effects in the market. Conclusions: Disincentive of reprehensible behavior derived from massive damage.